Effect of long-term training on heart rate variability, central hemodynamics and physical working capacity in female swimmers with different sports qualifications - Mykhaliuk, Ye. L.; Syvolap, V. V.; Horokhovskyi, Ye. Yu.; Михалюк, Євген Леонідович; Сиволап, Віктор Денисович; Гороховський, Є. Ю.; Михалюк, Е. Л.; Сыволап, В. В.; Гороховский, Е. Ю. (Запорізький державний медичний університет, 2021)
The aim of this study was to compare the indices of heart rate variability, central hemodynamics and physical working capacity in female swimmers with different sports qualifications. Materials and methods. The indices of heart rate variability (HRV), central hemodynamics (CH) and physical development (PD) were studied in 44 female swimmers (mean age 15.00 ± 0.36 years, swimming experience – 7.40 ± 0.35 years) depending on their sports qualifications (MSIC, MS, CMS, first- and second-class athletes). To analyze the autonomic regulation of cardiac activity, power spectral and time-domain indices of HRV were used. CH were examined by the method of automated tetrapolar rheography according to W. Kubiček et al. (1970) in Y. T. Pushkar’s et al. modification (1970). Physical working capacity was measured according to the generally accepted technique on a cycling ergometer using the PWC170 submaximal test. The functional state index (FSI) was calculated using the formula patented by authors. Results. Significant differences were found between the indices of HRV, CH and PD in female swimmers with different qualifications. Thus, in the athletes with the MSIC–MS sports qualifications, heart rate was 61.0 ± 3.8 bpm, cardiac index (CI) – 2.978 ± 0.098 L·min-1·m-2 (there was a trend towards the eukinetic type of hemodynamics (TH)), stress index (SI) – 51.16 ± 12.66 relative units (r.u.), PWC170/kg – 16.98 ± 1.22 kgm·min-1·kg-1, FSI – 6.511 ± 0.422 r.u. A decrease in heart rate among them was correlated with a decrease in SI, and an increase in Mo – with a decrease in CI. In female CMS swimmers, heart rate was 61.37 ± 2.83 beats/min-1, CI – 3.021 ± 0.112 l -1min -1·m -2 , a trend towards the predominantly eukinetic TH, SI – 53.73 ± 9.41 r.u., PWC170 /kg– 14.66 ± 0.683 kgm·min-1·kg -1, FSI – 5.683 ± 0.324 r.u. Reduced values of SI and CI were associated with increased values of Mo and PWC170/kg. In first- and second-class female swimmers, heart rate was 63.05 ± 2.22 beats/min, SI – 50.62 ± 6.4 r.u. This group tended to be eytonic and eukinetic. The mean value of the PWC170/kg was 14.19 ± 0.589 kgm·min-1·kg-1 and FSI – 5.953 ± 0.337 r.u. Correlation analysis confirmed the relationship between the decrease in heart rate and CI and the increase in Mo and PWC170/kg. Conclusions. Long-term training in female swimmers at the distance of 50 to 200 meters is accompanied by the significant increase in the PWC170/kg values with qualification improving, 14.19 ± 0.589 kgm·min-1·kg-1, 14.66 ± 0.683 kgm·min-1·kg-1; 16.98 ± 1.22 kgm·min-1·kg-1, respectively, improvements in HRV (decrease in stress index and increase in Mo) and decrease in CI. Мета роботи – порівняти показники варіабельності серцевого ритму, центральної гемодинаміки та фізичної працездатності у представниць плавання на короткі дистанції, які розрізняються за кваліфікацією. Матеріали та методи. Вивчили показники варіабельності серцевого ритму (ВСР), центральної гемодинаміки (ЦГ) і фізичної працездатності (ФП) у 44 плавчих (середній вік – 15,00 ± 0,36 року, стаж занять плаванням – 7,40 ± 0,35 року) залежно від спортивної кваліфікації (МС–МСМК, КМС, I–II розряд). Для аналізу вегетативної регуляції серцевої діяльності використовували часові та спектральні показники ВСР. Центральну гемодинаміку вивчали методом автоматизованої тетраполярної реографії за W. Kubiček et al. (1970) в модифікації Ю. Т. Пушкаря та співавт. (1970). Визначення фізичної працездатності здійснювали за загальноприйнятою методикою на велоергометрі з використанням субмаксимального тесту PWC170. Індекс функціонального стану (ІФС) розрахували за запатентованою авторами формулою. Результати. Виявили вірогідні відмінності між показниками ВСР, ЦГ і ФП у представниць плавання, які розрізнялися за кваліфікацією. Так, у плавців-жінок рівня МС–МСМК ЧСС була 61,0 ± 3,8 уд./хв, СІ – 2,978 ± 0,098 л·хв-1·м-2 (була тенденція до переважання еукінетичного ТК), ІН – 51,16 ± 12,66 ум. од., PWC170/кг – 16,98 ± 1,22 кгм·хв-1·кг-1, ІФС – 6,511 ± 0,422 відн. од. Зменшення частоти серцевих скорочень у них корелює зі зменшенням ІН, а збільшення Мо – зі зниженням СІ. Плавці-жінки кваліфікації КМС мають ЧСС 61,37 ± 2,83 уд·хв-1, СІ – 3,021 ± 0,112 л·хв-1·м-2, тенденцію до переважання еукінетичного ТК, ІН – 53,73 ± 9, 41 ум. од., PWC170/кг – 14,66 ± 0,683 кгм·хв-1·кг-1, ІФС – 5,683 ± 0,324 відн. од. Зниження ІН і СІ асоціюється зі збільшенням Мо і PWC170/кг. У плавчих кваліфікації II–I розряд ЧСС – 63,05 ± 2,22 уд·хв-1, ІН – 50,62 ± 6,4 ум. од., була тенденція до переважання ейтонії та еукінетичного типу кровообігу, PWC170/кг – 14,19 ± 0,589 кгм·хв-1·кг-1, ІФС – 5,953 ± 0,337 відн. од. Кореляційний аналіз підтвердив асоціацію зниження ЧСС і СІ зі збільшенням Мо і PWC170/кг. Висновки. Багаторічні тренування представниць плавання на дистанції від 50 до 200 метрів зі зростанням спортивної кваліфікації супроводжуються вірогідним збільшенням показників фізичної працездатності (PWC170/кг – 14,19 ± 0,589 кгм·хв-1·кг-1; 14,66 ± 0,683 кгм·хв-1·кг-1; 16,98 ± 1,22 кгм·хв-1·кг -1), позитивними зрушеннями ВСР (зниженням індексу напруги та збільшенням Мо) і зниженням СІ. Цель работы – сравнить показатели вариабельности сердечного ритма, центральной гемодинамики и физической работоспособности у представительниц плавания на короткие дистанции, которые различаются по квалификации. Материалы и методы. Изучены показатели вариабельности сердечного ритма (ВСР), центральной гемодинамики (ЦГ) и физической работоспособности (ФР) у 44 представительниц плавания (средний возраст – 15,00 ± 0,36 года, стаж занятий плаванием – 7,40 ± 0,35 года) в зависимости от спортивной квалификации (МС–МСМК, КМС, I–II разряд). Для анализа вегетативной регуляции сердечной деятельности использовали временные и спектральные показатели ВСР. Центральную гемодинамику изучали методом автоматизированной тетраполярной реографии по W. Kubiček et al. (1970) в модификации Ю. Т. Пушкаря и соавт. (1970). Определение физической работоспособности осуществляли по общепринятой методике на велоэргометре с использованием субмаксимального теста PWC170. Индекс функционального состояния (ИФС) рассчитывали по запатентованной авторами формуле. Результаты. Выявлены достоверные различия между показателями ВСР, ЦГ и ФР у пловчих, которые различаются по квалификации. Так, у пловцов-женщин уровня МС–МСМК ЧСС была 61,0 ± 3,8 уд./мин, СИ – 2,978 ± 0,098 л·мин-1·м-2 (имелась тенденция к превалированию эукинетического ТК), ИН – 51,16 ± 12,66 усл. ед., PWC170/кг – 16,98 ± 1,22 кгм·мин-1·кг -1, ИФС – 6,511 ± 0,422 отн. ед. Уменьшение ЧСС у них коррелирует с уменьшением ИН, а увеличение Мо – со снижением СИ. Пловчихи квалификации КМС имеют ЧСС 61,37 ± 2,83 уд.·мин-1, СИ – 3,021 ± 0,112 л·мин-1·м-2, тенденцию к превалированию эукинетического ТК, ИН – 53,73 ± 9,41 усл. ед, PWC170/кг – 14,66 ± 0,683 кгм·мин-1·кг-1, ИФС – 5,683 ± 0,324 отн. ед. Снижение ИН, СИ ассоциируется с увеличением Мо и PWC170/кг. У пловцов-женщин квалификации II–I разряд ЧСС – 63,05 ± 2,22 уд./мин, ИН – 50,62 ± 6,4 отн. ед., была тенденция к превалированию эйтонии и эукинетического типа кровообращения, PWC170/кг – 14,19 ± 0,589 кгм·мин-1·кг-1, ИФС – 5,953 ± 0,337 отн. ед. Корреляционный анализ подтвердил ассоциацию снижения ЧСС и СИ с увеличением Мо и PWC170/кг. Выводы. Многолетние тренировки представительниц плавания на дистанции от 50 до 200 метров с ростом спортивной квалификации сопровождаются достоверным увеличением показателей физической работоспособности (PWC170/кг – 14,19 ± 0,589 кгм·мин-1·кг-1; 14,66 ± 0,683 кгм·мин-1·кг-1; 16,98 ± 1,22 кгм·мин-1·кг-1), позитивными сдвигами ВСР (снижением индекса напряжения и увеличением Мо) и снижением СИ.
Вплив довготривалих тренувань на варіабельність серцебиття, центральну гемодинаміку та фізичну працездатність жінок-плавців із різними спортивними кваліфікаціями
Влияние длительных тренировок на вариабельность сердечного ритма, центральную гемодинамику и физическую работоспособность пловчих разной спортивной квалификации
Михалюк Є. Л. - ORCID ID: 0000-0003-3607-7619; Сиволап В. В. - ORCID ID: 0000-0001-9865-4325.
Keywords: swimming; female; athletes; correlation; плавання; жінки; спортсмени; кореляція; плавание; женщины; спортсмены; корреляция